Dyadic gift-giving behaviour: dimensions, relationships and motivations from an attachment perspective - Ines, Branco-Illodo (2016)
Dyadic gift giving is often described as a mechanism to manage important but insecure relationships (Caplow, 1982). Considering that most gift giving behaviour happens within interpersonal relationships (Ruth, 1996), and that the economic significance of the gift market in the UK represents £40 billion in 2012 (Mintel, 2013), it is important to understand how relationships operate as antecedents of gift giving behaviour.